Kajian Analisis SWOT Potensi Unggulan Budidaya Perairan Payau Kabupaten Sukamara, Provinsi Kalimantan Tengah - Suriansyah Suriansyah; Evi Veronika; Hermansyah Hermansyah (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2022)
The potential for brackish water cultivation in Sukamara Regency which can be used as prime commodities is milkfish and vannamei shrimp due to the availability of the carrying capacity of the waters and the area of land in Jelai District and Pantai Lunci District. In addition to this, the availability of labor, strategic business locations, post-harvest handling, local and national market share at high economic prices. The results of the SWOT analysis study show that the SO Strategy (Strengths Opportunities) can apply the external factors of brackish water milkfish and vannamei shrimp cultivation, because it already has marketing network opportunities, technology, product quality, business development and government support that can be utilized for the development of leading businesses in the future. in the future, because it is classified as a strategy that uses internal strengths to take advantage of external opportunities that are already available. Keywords : Potential for brackish water cultivation, milkfish, vannamei shrimp